Application of E-Learning System for Teachers and Vacational Students to Improve the Quality of Learning in Realizing the School Concept Based On Information and Communication Technology - Kusnarto; A. Pratama; E. Solihatin (Nusantara Science and Technology Proceedings)
E-learning as a new learning model in education provides a great role and function for the world of education. It answers the shortcomings and weaknesses of conventional education (education in general) including the limitations of space and time. Information technology that has a standard internet platform can be a solution to these problems because of the nature of the internet, which allows everything to be connected, cheap, simple and open so that the internet can be used by everyone, everywhere, everytime and free to use (available to every one). The problems that are faced by our partners (Poncol and 2 Vocational High School of Magetan) are they have electronic devices (computers and wifi) but do not have e-learning, and also, the need of increasing teachers human resource. The objective of this Community Service Research Program is to 1) make chamilo-based e-learning media partners; 2) improve the ability of teachers and students to apply chamilo-based e-learning for actualizing the concept of ICT-based schools; and 3) increasing teacher and student interaction without limits of space and time (via online, anytime and anywhere). The method used is Participatory Rural Appraisal (PRA) method by involving more partner participants facilitated by community service programs UPN Veteran Jawa Timur as resource / facilitator for the implementation of chamilo-based E-Learning. The results of the Community Service Research Results Program are 1) Partners have chamilo-based e-learning media; 2) Teachers and students have been able to apply chamilo-based e-learning for actualizing the concept of ICT-based schools; also 3) the teacher and student interactions have increased without limits of space and time (online, anytime and anywhere). Based on implementation of this program, it was concluded that the e-learning system is useful to improve the quality of teacher and student learning for actualizing the concept of information and communication technology-based schools.